Graphene Oxide on the Microstructure and Mechanical Properties of Cement Based Composite Material - Pang Jinchang; Wang Yeming (Fracture and Structural Integrity)
To investigate the mixing amount of graphene oxide and water cement ratio on the microstructure and mechanical properties of graphene oxide reinforced cement based composite material, graphene oxide suspension was developed using improved Hummers method, and the structure, size and morphology of graphene oxide were represented using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and AFM. The results demonstrated that the bending and compressive strength of graphene oxide reinforced cement based composite material improved firstly and then declined with the increase of the mixing amount of graphene oxide, and moreover the improvement of the bending strength was obvious than that of the compressive strength. When the content of graphene oxide was 0.03%, the bending strength reached the maximum, 13.73 MPa. Under a high water cement ratio, the addition of graphene oxide was more effective in enhancing the strength of cement mortar. The representation of the microstructure of cement based composite material with scanning electron microscope (SEM) suggested that graphene oxide could optimize the microstructure of cement hydration products, improve the pore structure of set cement, reduce the volume of micropore in set cement, and increase the compactness of set cement, i.e. apparently strengthen the toughening effect of set cement. The research achievements are useful to improve the mechanical properties of cement based composite materials.